Денежно-весовая система обращения в древней Палестине в I-й половине I тысячелестия до н.э. - Амусин, И. Д. (1973)
Amusin, J. D.; The system of weights as monetary units in ancient Palestinian currency in the first half of the first Millennium B.C.; engl. Résumé S. 233.